Automatic identification of music performer using the linear prediction cepstral coefficients method - Magdalena CHUDY (Archives of Acoustics)
The paper describes a method of automatic identification of different music performers playing identical pieces of music on the same instrument. The performers' models based on the LPCC features and vector quantization are proposed as methods of classification. The presented approach was verified with a database of experimental samples of Bach's 1st Cello Suite recorded especially for this study and the original audio CD recordings of Bach's 6 Cello Suites performed by six famous cellists.